GRP-042 Computerized Physician Order Entry in the Geriatric Center: Collection and Analysis of Prescribing Errors Made Over a 5-Month Period. (12th March 2013) - Cool, C; Lebaudy, C; Laborde, C; Cestac, P
Abstract : Background: Following the total computerization of prescriptions in the Geriatric Center over the past two years, the pharmaceutical team performs a pharmaceutical analysis for all the beds in the centre every day. Computerization is capable of reducing prescribing errors but it can generate some risks. Purpose: To collect, analyse and code the prescribing errors detected over a 5-month period, and to deduce the necessary actions to be taken in order to reduce the number and occurrence of errors. Materials and Methods: Research was carried out over the entire Geriatric Center: 314 beds (short, medium and long stays). Prescribing errors were collated daily and analysed via the computerised prescription software Disporao©. The proposed pharmaceutical interventions were communicated daily to the medical and care teams. The analysis and coding of the errors were carried out with an Excel© spreadsheet which logs a range of criteria, such as the patient's sociodemographic background, the drug(s) involved, the type of error, the associated pharmaceutical intervention and many others. Results: 60 errors for 1000 patient days, that is 0.5 error per stay and 90 errors per 1000 prescriptions were detected for short stays. 1393 errors of all types were detected over 5 months, which is 0.9 error per month and per bed. The errors were spread over 3 categories: errors defined by the French Clinical Pharmacy Society criteria (67.3%), errors linked to the computerised tool (14.3%) and other types of error (18.4%). 5 drug classes were heavily involved. 59% of patients were affected by an error despite a prior pharmaceutical intervention. Errors rarely have drastic consequences on the patient: 4‰ prescriptions. Weaknesses in knowledge and malpractice represent nearly 85% of the total of errors. Errors due to computer parameters represent an increasing risk (14%). Conclusions: Most prescribing errors are avoidable. Although computerised physician order entry is a way of making the medication process safer, it also generates comments and has limitations. The prescription tool determines the type and frequency of errors. All these errors justify the analysis of all the prescriptions by a pharmacist, as s/he has a rounded knowledge of the patient beyond the medical prescription. The booming certification of various software packages dedicated to helping hospital prescription writing in a way acceptable to the High Authority for Health contributes to this step of making care safer and will hopefully lead to a decrease in errors. No conflict of interest.